Constraints on the appearance of a maximum in astrophysical S-factor; Physics Letters B; Vol. 824 - Sargsyan V. V. Vazgen Valerikovich; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Lenske H. Horst (2022, 2022)
Title screen